Better decisions through enhancing decision-makers? Moral enhancement and liberal democracies - Huttunen, Henri (My University, 2019)
At the beginning of the 21st century, humanity faces multiple unprecedented global dilemmas that defy easy solutions and call into question the ability of the liberal democracies to rise to answer them. At the same time, advancements in sciences and technology have made it possible for humans to shape their own biology like never before, sparking a discussion on the ethical permissibility of humans seeking to enhance themselves or their descendants. Set against this background, the purpose of this thesis is twofold. First, to give a general overview of the so-called human enhancement debate, analyzing arguments for and against enhancement interventions and weighing their merits and weaknesses. Second, to advance an argument that the introduction of a particular type of enhancement, moral enhancement, is desirable from the point of view of generating morally more responsible political decisions.
Keywords: human enhancement, moral enhancement, bioethics, political philosophy, democracy